(untitled) (Journal of the College of Basic Education, 2022)
The development of any sports game and its access to the required level depends on the concerted efforts and the elimination of all the problems facing the game and the removal of all the negatives in order to raise its level. "Studies in the field of psychology have proven the close relationship between the level of mental abilities and the superiority of the athlete." ( )The game of basketball is one of the team sports that has achieved a wide spread around the world because of its educational, physical, skill and mental advantages and characteristics, in addition to the presence of its own elements such as excitement, vital technical performance, and fun for its practitioners as well as for the spectators, hence it was necessary to be careful proper planning of the training process